2020
DOI: 10.1080/13691058.2020.1795266
|View full text |Cite
|
Sign up to set email alerts
|

Parent, partner and individual contexts of very early first sex experiences among young men and their links to subsequent reproductive health outcomes

Abstract: Research indicates that upwards to 30% of US urban Black male adolescents report first sex younger than age 13; however, there is limited literature on the sexual and reproductive health outcomes and contexts of these early first sex experiences. This exploratory study described sexual and reproductive health histories and explored personal, partner and parent contextual factors associated with first sex experiences occurring at 13 years or younger among a sample of US urban young men aged 15-24. Participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 45 publications
(60 reference statements)
2
1
0
Order By: Relevance
“…Regarding the partner-relationship maintained at the first instance of sexual intercourse, participants in the present study reported that they were mostly part of a stable couple, followed by being friends with the partner, with a minority response of engaging with strangers. These data coincide with reports by Offiong et al [24] and Spinola et al [2]. Regarding the couple relationship, no differences were observed between sexes or cultural groups.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Regarding the partner-relationship maintained at the first instance of sexual intercourse, participants in the present study reported that they were mostly part of a stable couple, followed by being friends with the partner, with a minority response of engaging with strangers. These data coincide with reports by Offiong et al [24] and Spinola et al [2]. Regarding the couple relationship, no differences were observed between sexes or cultural groups.…”
Section: Discussionsupporting
confidence: 92%
“…Referring to the age of sexual debut, the young people in this study had their first intercourse at 16.44 years, a mean that coincides with numerous international studies [19][20][21][22][23][24][25][26][27]. Early onset of intercourse is associated with a higher prevalence of risky sexual practices and a higher incidence of contracting sexually transmitted infections and unintended pregnancies [19].…”
Section: Discussionmentioning
confidence: 53%
“…Regarding the age of onset of sexual relations, the young people studied had their first sexual intercourse at 16.34 years of age, similar to that of numerous international studies [ 20 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. Studies suggest that viewing sexual content is a key factor contributing to early sexual intercourse as well as fostering negative attitudes towards contraceptive methods, particularly barrier methods [ 20 , 32 , 33 ].…”
Section: Discussionsupporting
confidence: 69%